Bank runs, liquidity and credit risk - Jukka Topi (Bank of Finland, 2008)
In this paper, I develop a model that addresses the links between banks liquidity outlook and their incentives to take credit risk. Assuming that both bank-specific liquidity shocks and credit losses are necessary to provoke bank runs, the model predicts that a bank s incentives to mitigate its credit risk by screening decrease if the probability of a bank-specific liquidity shock declines. This suggests that the benign liquidity outlook prevailing prior to the subprime crisis may have contributed to the lack of screening by banks that has been an important causal factor in the crisis.
URN:NBN:fi:bof-20140807151
Keywords: 330